Dairy Goat Sector Enhancement Strategies for Sustainable Livestock Farming Communities - Kikwatha, Reuben; Kyalo, Ndunge (University of Nairobi, 2020)
Livestock production remains a critical sector in the agricultural economy of developing countries. Among the livestock production systems, dairy goat production has increasingly gained popularity as a significant contributor to this important sector. Innovation and adoption of new technologies, such as the promotion of dairy goat production and the improvement of indigenous goats for better production, are poised to make an even bigger contribution. This is in particular to the Kenya Big Four Agenda focused on eradicating extreme poverty and hunger, promoting gender equality, ensuring universal health care for citizens and habitable housing as well and tackling climate change by 2030.
Keywords: Agriculture; Kenya